Dialogue, Confrontation of Knowledges and Cultural Negotiation. Core Ideas of Popular Education Pedagogies: An Elaboration from the South - Marco Raul Mejía (Universidad Pedagógica Nacional, 2016)
Pedagogical discourses on popular education were woven from the questioning to lancasterianismo, which is present in Simón Rodríguez's approaches and develops in the quest of American peoples to building an Indoamerican thinking. An axample of this process can be found in the Warisata School, which gets an interesting dimension in the light of Paulo Freire's writings. The concept of dialog of knowledges makes interculturalism and cultural negotiation possible, two fundamental elements for a transforming educational action.